Adventures in indigence, and other essays - Portor, Laura Spencer, 1872-1957 (Salt Lake City, UT : Project Gutenberg, 2023)
"Adventures in Indigence" by Laura Spencer Portor is a collection of essays written in the early 20th century. The essays recount the author's personal experiences with the poor and marginalized, exploring themes of empathy, social observation, and the intrinsic values of those who face hardship. Portor offers reflections that challenge conventional views on poverty and the power dynamics surrounding it. The opening of the collection introduces the first essay titled "Musgrove," where the author reminisces about her childhood encounters with poverty and the significant figures that shaped her understanding of the poor. She recounts her mother's compassion towards a man named Musgrove, who was characterized by a series of unfortunate events that seemed to follow him. Portor reflects on the profound impact that these encounters had on her perception of the poor, emphasizing their resilience and the complex experiences they brought into her life. This sets the tone for a narrative that goes beyond mere charity to delve into the deeper human connections formed through the lens of poverty. (This is an automatically generated summary.)
Adventures in indigence: Musgrove. The harp and the violin. Major Lobley. Mamie Faffelfinger. The lure of the "chiffoneer." Margaret. Margharetta. The powers of the poor. Horatio -- Guests: Relations of the spirit. Kith and kin -- The disappointments and vicissitudes of mice -- Birthdays and other egotisms.
Release date is 2023-01-27
hekula03 and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: American essays -- 20th century